Addressing neurodynamic irritability in a patient with adhesive capsulitis: a case report. (1st January 2017) - Farrell, Kevin; Lampe, Katherine
Abstract : Background: Patients with adhesive capsulitis are commonly seen by physical therapists. Pain and limited shoulder motion from adhesive capsulitis have at times been linked to neural irritation. The purpose of this case is to describe the examination and intervention of a patient with adhesive capsulitis who appeared to have a coexisting, underlying neural irritation. This paper emphasizes how the neurological component must initially be identified and addressed for a successful outcome. Case description:: A 47-year-old female presented with reduced shoulder motion and function, upper extremity neural irritation, diffuse weakness, altered sensation in the involved extremity, and symptoms reproduced with upper limb neurodynamic testing. Her reduced shoulder range of motion was accompanied by limited glenohumeral glides and a report of local neck stiffness. Symptoms began several months earlier after an apparent electrical shock injury to the arm that caused symptoms and guarding of the shoulder. Intervention initially addressed the underlying neural component with spinal mobilizations while avoiding further irritation. Interventions were progressed to include mobilization and exercise to address shoulder mobility. Outcomes:: The patient's neurodynamic irritability, distal symptoms, and neck stiffness were normalized within the first weeks of care. Subsequently, interventions were directed at the shoulder. Outcomes over an 12-week time frame included reduced pain from 10/10 to 2/10. Passive range of motion increases included flexion from 121 to 160°, abduction from 71 to 121°, and external rotation from 18 to 60°. Disability scores on Disabilities of the Arm, Shoulder, and Hand (DASH) dropped from initially 68·3 to 18·3% at discharge. She ultimately regained full upper extremity function. Discussion:: Therapists should be cognizant of possible neural irritation in shoulder disorders, which may contribute to conditions such as adhesive capsulitis. Identifying neural irritation is critical when determining which interventions will achieve optimal outcomes without aggravating the condition.